High-Yielding Regioselective Synthesis of Coumarin/2-Quinolone C3–C4 Fused 5-Substituted-1,4-Benzodiazepine Scaffolds - Nagamani, Vediyappan; Kamaraj, Sriraghavan (Synthesis, 2025)
Herein, we report an unprecedented route for the high-yielding regioselective synthesis of coumarin/2-quinolone C3–C4 fused 5-substituted-1,4-benzodiazepine scaffolds via indium chloride-mediated Pictet–Spengler type cycloannulation of 3-amino-4-(phenylamino)-coumarin/2-quinolone and aryl/heterocyclic aldehydes through the transitory intermediacy of the cyclic diamine–indium complex. Also, a plausible mechanistic pathway has been proposed from control experiments and HRMS analysis of reactive intermediates. This robust protocol eases access to the structurally diversified, privileged, seven-membered skeleton with an excellent step economy.
Keywords: Coumarin/2-quinolone; Regioselective synthesis; Indium(III) chloride; Cyclic diamine–indium complex; 1,4-Benzodiazepines